Have we made any headway in the diagnosis of neurotuberculosis? Place of real time PCR or real time PCR - Aggarwal, Mukul; Aggarwal, Kailash C.; Nair, Deepthi (Journal of Pediatric Infectious Diseases, 2012)
The diagnosis of Central Nervous System tuberculosis (CNS TB) had been always an enigma as yield of Mycobacterium tuberculosis in cerebrospinal fluid (CSF) is very low and diagnosis mainly rested on combination of clinical, CSF analysis and radiological findings. We attempted to find whether 16s rRNA primer based real time Polymerase chain reaction (PCR) aids in diagnosis of tubercular meningitis (TBM) and tuberculoma. Literature is flooded with newer techniques for the diagnosis of neuro-tuberculosis by real time PCR. But no clear cut guidelines are available about their role. 40 cases of tubercular meningitis, diagnosed on basis of Modified Ahuja Criteria and 40 controls were included in this prospective study. All patients were evaluated clinically and investigated in detail including cerebrospinal fluid analysis, Acid Fast Bacilli staining, culture for TB by Bac T Alert 3-D system,16s rRNA real time PCR assay, chest X ray, computed tomography scans of head, contact survey using chest X-ray, Mantoux test and hemogram. Comparative analysis of real time PCR were done in control group vs. cases of TBM diagnosed on the basis of Modified Ahuja criteria. Results: CSF for tuberculosis by real time PCR was positive in 26/40 cases (65%) of TBM, as against 2/40 controls. Keeping the CSF culture as the gold standard its sensitivity is 62.50 (95% confidence intervals- 54.7, 85.2), specificity is 77.40 (95% confidence intervals- 54.7, 85.2), positive predictive value is 46.15 and negative predictive value is 88.89. Modified Ahuja criteria can serve as useful tool in diagnosis. CSF analysis by real time PCR has shown better sensitivity and quicker results than culture. However, it cannot be recommended alone as it was negative in about a third of cases. But its significance is underlined in early diagnosis and as an adjunct to culture.
Keywords: Real time polymerase Chain reaction; neurotuberculosis; cerebrospinal fluid analysis; tubercular meningitis; tuberculoma